2022
DOI: 10.3390/ma15196842
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Nano-Hydrophobic Admixture on Concrete Durability and Steel Corrosion

Abstract: Steel corrosion is major reason of the deterioration of reinforced concrete structures. Decreasing the transportation of erosion ions in concrete is one of effective methods to protect the steel from corrosion. In the present work, a novel nano-hydrophobic admixture is introduced to improve the ion-diffusion properties and the corrosion resistance of reinforced steel. Compared with unmodified concrete, the nano-hydrophobic admixture effectively decreases the water adsorption, water evaporation, and chloride io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Cai et al [63] and Li et al [64] both explored the use of nano-hydrophobic materials in concrete for enhanced durability and corrosion resistance. Cai's study revealed a substantial reduction in water adsorption (>78%) and a doubling of the initial corrosion time for steel reinforcement.…”
Section: Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai et al [63] and Li et al [64] both explored the use of nano-hydrophobic materials in concrete for enhanced durability and corrosion resistance. Cai's study revealed a substantial reduction in water adsorption (>78%) and a doubling of the initial corrosion time for steel reinforcement.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…This interaction highlights the potential for improved corrosion protection of reinforcement in concrete structures through the strategic use of silane-modified materials. Cai et al [63] studied the impact of a nanohydrophobic admixture (TIA) on the durability of concrete and corrosion of steel using electrochemical measurements. TIA delayed initial corrosion onset, extending it by over one cycle with 30 kg m −3 TIA.…”
Section: Impact On Reinforcement Corrosion Of Bmhcmentioning
confidence: 99%
“…Alternatively, much attention has been paid to the introduction of inorganic nanomaterials or hydrophobic organic components with specific advantages. Although inorganic nanomaterials such as nano-SiO 2 [ 6 , 7 ], TiO 2 [ 8 ], Fe 3 O 4 [ 9 ], and carbon nanomaterials [ 10 ] can fill the connecting pores and reduce the harmful pores, the serious aggregation of nanomaterials in cement slurries and required high dosage amount may cause limited effects, increased shrinkage and poor workability [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The next strategy involves using a coating to prevent water from contact with the concrete. Ionic varnishes, edge varnishes, and ground varnishes are mostly included [3]. The design of concrete products as well as the causes of hybrid cracking have been the focus of the bulk of nano-research in building projects.…”
Section: Introductionmentioning
confidence: 99%